Evaluation of Accounting Information System Using Usability Testing Method and System Usability Scale - Putri, Rozza Maudina Ayuwan; Parwita, Wayan Gede Suka; Handika, I Putu Susila; Sudipa, I Gede Iwan; Santika, Putu Praba (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The computer-based accounting information system IBS Core has been used by Renon Pekraman Village Credit Institution since 2016 to facilitate all transaction processes. This study aims to evaluate the usefulness of the IBS Core accounting information system, determine the effectiveness, efficiency, and user satisfaction with the IBS Core accounting information system, and identify areas that need improvement in the IBS Core accounting information system.The method used in this study is Usability Testing using performance measurement and retrospective think aloud (RTA) as well as the System Usability Scale (SUS). The results of the study show that the IBS Core system has a high effectiveness score of 92.50%. The average time required for participants to complete the task scenario is 68.9 seconds, and users feel that the available content is clear and consistent. In addition, the average System Usability Scale (SUS) score is 86.125, where the results were above the standard average SUS score. The IBS Core System Score was ranked B with the adjective ratings "Excellent” Next, the acceptability ranges are included in the "Acceptable" category, and finally the net promote score (NPS) is included in the "Promoter" category, showing that the use of the IBS Core system gets a very good assessment from its users. This shows that the IBS Core system is highly appreciated and considered very useful by its users.